Pengaruh Rasio Keungan Terhadap Kinerja Keungan pada PT Bank Syariah Indonesia TBK - Munti Metralia; Sindi Aprilia; Dira Oktarini; Dola Andini (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2025)
This study is intended as an effort to evaluate the extent to which financial ratios affect the performance of PT Bank Syariah Indonesia Tbk (BSI) during the period 2021 to 2024. The focus of the study covers four main ratios, namely Financing to Deposit Ratio (FDR), Non-Performing Financing (NPF), Capital Adequacy Ratio (CAR), and the ratio of Operating Costs to Operating Income (BOPO). Financial performance is measured using two indicators, including Return on Assets (ROA) and Return on Equity (ROE). The approach used is quantitative descriptive by applying multiple linear regression analysis and F-tests and t-tests in order to determine the simultaneous and partial effects. Findings from the analysis results show that the four ratios collectively have a real impact on ROA and ROE. Individually, FDR has a positive and significant impact on ROA, while NPF and BOPO have a negative impact on financial performance. Meanwhile, CAR has a positive impact on ROA, although the level of significance is inconsistent. This finding emphasizes the importance of effective management of financial ratios to improve BSI's profitability and efficiency. This also supports the achievement of the Bank's strategic objectives as a competitive Islamic financial institution at the global level.